New heights in Indo-U.S. relations - Das, P. K. (Jaipur, 2005)
This book highlights the latest developments in the field of Indo-U.S. relations. The book highlights the increase in trust between the two Govts. and the people of India and U.S. trade and commerce has increased mainfold between India and US in the recent past. All these aspects make the Indo-U.S. relations very important and impressing.
Keywords: India - foreign relations - United States